The Implementation of the Teaching Campus Program on Students' 21st Century Skills: A Systematic Review - Rohmalia Hayatun Nufus; Riesta Octoviani; Siti Eliyana; Indah Juwita Sari (Jurnal Pendidikan Indonesia Gemilang, 2023)
This study aimed to determine the implementation of the Teaching Campus Program on 21st century skills of college students and students. This study used a systematic review which was conducted by reviewing several articles to answer research questions. The research question is". The result showed that the implementation of the Campus Teaching Program on 21st century skills for college students are to address confidence, initiative, creativity and innovation, communication, cooperation, discipline, and technology adaptation. Additionally, the implementation of the Campus Teaching Program on 21st century skills for school students is to address numeracy literacy and technology adaptation.